Comparative study of knowledge about oral cancer among undergraduate dental students - Samara Ribeiro da Silva; Yara Juliano; Neil Ferreira Novo; Ilan Weinfeld (Einstein (São Paulo))
ABSTRACT Objective: To evaluate and compare the knowledge of dental undergraduate students about oral cancer. Methods: The students were divided into two groups according to semester attended in the undergraduate course: Group A, the first semester; and Group B, seventh semester. They were asked to answer a questionnaire about epidemiology, risk factors, clinical aspects, therapeutic solutions and oral self-examination. For statistical analysis, the Fisher's exact test, the Cochran's G test and Kendall's concordance test were used, with significance level set at 0.05. Results: Regarding the prevalent sex, only 8.0% of Group A and 56.0% of Group B judged males as the frequent affected by the disease (p=0.0006). In terms of age, 84.0% of the Group B and 44.0% of the Group A estimated that most cases were diagnosed over 40 years (p=0.0072). Smoking was identified as the major risk factor for 64.0% and 91.6% of Groups A and B, respectively (p=0.0110). On issues related to sex, ethnicity, age, risk factors, self-examination, treatment, professional responsible for treatment and profile of an individual with the disease, the seventh-semester showed significantly higher correct answer percentages than first-semester undergraduates. Conclusion: There was significant correlation between the right and wrong answers given by first and seventh semester students, making necessary a specific approach directed to their lack of knowledge.